Embedding the delivery of antenatal vaccination within routine antenatal care: a key opportunity to improve uptake. Issue 5 (3rd May 2020) - Wilcox, Christopher R; Woodward, Charlotte; Rowe, Rebecca; Jones, Christine E
ABSTRACT: Improving the uptake of vaccination in pregnancy has been highlighted as a priority by the World Health Organisation, yet establishing the optimal location for delivery of the antenatal vaccination program remains a topic of debate internationally. In many countries, antenatal vaccines are usually delivered within Primary Care (under the lead of general practitioners [GPs] or family physicians), yet this often presents a logistic barrier to accessing vaccination, and increasing evidence demonstrates that embedding vaccination within routine antenatal care visits may significantly improve uptake. In this commentary, we discuss recent evidence to support this approach, including anonymous feedback from patients and staff at our own institution, in which a dedicated midwife-led vaccine clinic has recently been set up. Furthermore, we highlight a number of individual and institution-level barriers which would need addressing before this approach can be routinely adopted, and suggest targets for future education and research.